Life is not an accident a memoir of reinvention - Williams, Jay 1981- (Harper, 2017)
Ten years ago Williams was at the beginning of a brilliant professional basketball career, the Chicago Bulls' top draft pick. Then he ran his motorcycle head-on into a light pole, severely damaging himself and ending his career. In this intense, hard-hitting, and deeply profound memoir Williams talks about the accident that transformed him from a kid who had it all, thought he was invincible, and lost everything ... only to gain new wisdom. He shares behind the scenes details of life as an All-American, but also introduces us to a dark underworld culture in the pros: the gambling, drugs, and sex in every city, with players on every team.